(untitled) (Global Journal of Human-Social Science, 2013)
Nowadays English language and culture have grabbed every nucleus of almost all the University students in Bangladesh In Bangladesh English is taught as a compulsory subject in schools colleges and in universities i e from the primary level to the tertiary level The students of Jahangirnagar University in Bangladesh are no exception Here the students think that using English not only facilitates communication but also help them do well in their future life Some students think that it is a way to show smartness Out of all these the present researcher seeks to find out the impact and influence of the English language on the lifestyle of the tertiary level students in Bangladesh It also tries to prove the fact that English language is a machine or a tool of domination and power The paper briefly discusses the origin of English language in the Indian subcontinent and in Bangladesh It also refers to the works done on the same area by different researchers Then it provides an overview or an analysis of some questions to sort out the use of English by the students It finds out in what ways the students use English language At last it offers some recommendations and solution to get out of the influence of the English language